URGENSI PERLINDUNGAN HUKUM TERHADAP PENGGUNA JASA TRANSPORTASI ONLINE YANG MENJADI KORBAN TERJADINYA TINDAK PIDANA DI INDONESIA - Panjaitan, Hertavip Dewantara; Artina, Dessy; Elmayanti, Elmayanti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
The important role of this transportation service can be seen by the increasing need fortransportation services for the mobility of people and goods from and throughout the country. But thepresence of online transportation, both online motorcycle taxis and online taxis, has a chaotic existencewhich never stops accompanied by various controversies. Therefore, the urgency of legal protection forusers of online transportation services who are victims of criminal acts requires legal reform that regulatesthe legal protection of users of online transportation services who are victims of criminal acts in Indonesia.Given the development of our transportation at this time continues to grow, especially the existence ofonline transportation that is still not clearly and clearly regulated.This type of research is normative juridical research that is research conducted by examiningliterature discussion with secondary data sources consisting of primary legal material in the form of lawsand regulations, secondary legal material legal books, and tertiary legal material in the form of adictionary. Then the data were analyzed qualitatively, namely analyzing descriptive data obtained fromsecondary data.From the results of the study it can be concluded that, first, that the legal arrangements againstcrimes committed by online transportation in Indonesia use regulations, such as the Criminal Code andsometimes also online transportation is inseparable from Law Number 8 of 1999 Concerning ProtectionConsumer. Until now there has been no regulation that specifically regulates the existence of onlinetransportation. Where the new government is able to make a regulation in the form of MinisterialRegulation No. 12 of 2019 concerning the protection of the safety of motorcycle users which is used for thebenefit of the community. Second, the urgency of legal protection for users of online transportation serviceswho are victims of criminal acts is needed. This is because the company and the government seem to payless attention to the rights of users of online transportation services, especially those who are victims ofcriminal acts committed by online transportation drivers which cause material or immaterial losses.Keywords: Urgency - Legal Protection - Users of Online Transportation Services - Victims -Criminal Acts